2018
DOI: 10.7554/elife.31522
|View full text |Cite
|
Sign up to set email alerts
|

MukB ATPases are regulated independently by the N- and C-terminal domains of MukF kleisin

Abstract: The Escherichia coli SMC complex, MukBEF, acts in chromosome segregation. MukBEF shares the distinctive architecture of other SMC complexes, with one prominent difference; unlike other kleisins, MukF forms dimers through its N-terminal domain. We show that a 4-helix bundle adjacent to the MukF dimerisation domain interacts functionally with the MukB coiled-coiled ‘neck’ adjacent to the ATPase head. We propose that this interaction leads to an asymmetric tripartite complex, as in other SMC complexes. Since MukF… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
93
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(102 citation statements)
references
References 65 publications
(150 reference statements)
9
93
0
Order By: Relevance
“…Here we developed several systems to prove and analyse the interaction between Nse4 and SMC6. We mapped the Nse4-SMC6 interface in detail and found that the Nse4-SMC6 interaction mode is similar to the other νSMC-kleisin interactions [1618, 26, 34]. Therefore, we assume that Nse4 bridges SMC5-SMC6 proteins in a way similar to kleisins in the other SMC complexes, except that the Nse4 bridge is specifically modulated by the Nse1-Nse3 KITE subunits in the SMC5/6 complex (see below).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Here we developed several systems to prove and analyse the interaction between Nse4 and SMC6. We mapped the Nse4-SMC6 interface in detail and found that the Nse4-SMC6 interaction mode is similar to the other νSMC-kleisin interactions [1618, 26, 34]. Therefore, we assume that Nse4 bridges SMC5-SMC6 proteins in a way similar to kleisins in the other SMC complexes, except that the Nse4 bridge is specifically modulated by the Nse1-Nse3 KITE subunits in the SMC5/6 complex (see below).…”
Section: Discussionmentioning
confidence: 92%
“…Next, we took advantage of the crystal structures of the kleisin-νSMC complexes [1618, 26, 34], which suggest a key role for the N-terminal HTH domain of the kleisin molecule in its binding to νSMC neck. We mutated residues within the third α-helix of the Nse4 HTH domain (aa62-68) and analysed their impact on the Nse4-SMC6 interaction using the SMC5-Nse4-SMC6 3Y2H system as above (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Formation of such complexes could lead to effectively two-sided extrusion and gapless chromosome compaction. In prokaryotes, such as E. coli (which have MukBEF complexes, SMC complex homologs), experiments show that MukBEF forms dimers of complexes (Badrinarayanan et al, 2012) linked by the kleisin molecule, MukF (Zawadzka et al, 2018) . MukBEF complexes promote long-ranged contacts within E. coli chromosome arms (Lioy et al, 2018) , and they are proposed to function by two-sided loop extrusion.…”
Section: Oligomerization Of Smc Complexesmentioning
confidence: 99%
“…MukBEF acts as a dimer of SMC dimers when it is loaded onto DNA, which are connected by an N‐terminal mediated dimerization of the kleisin MukF . Their proposed form of action is a “rock climbing” movement on two DNA strands to generate LEF activity (Figure c), where staggered topological entrapment, followed by extrusion of DNA through the kleisin interface of two SMC complexes in close proximity would generate loop extrusion …”
Section: Biophysical Models For Smc Complexes Acting As Lefsmentioning
confidence: 99%